Organizational Communication Patterns in Inceasing Solidarity Between Members Among Youth at the Annisul Muttaqin Mosque, Bedewang Village, Banyuwangi Regency - Ananda Febri Darulia Putri; M. Dimyati Huda; Prima Ayu Rizqi Mahanani (Journal of Communication, Sustainability, and Empowerment, 2026)
An organization is a collection of individuals united by common goals, where communication plays a crucial role in strengthening relationships among members. Ineffective communication patterns, however, may lead to conflict and weaken organizational sustainability. This study aims to analyze communication patterns, solidarity values, as well as supporting and inhibiting factors in fostering solidarity among the youth of Annisul Muttaqin Mosque, Bedewang Village, Banyuwangi Regency. Using a qualitative approach, data were collected through observation, interviews, and documentation with eight informants consisting of administrators and youth members. Data analysis followed the stages of data collection, reduction, display, and conclusion drawing. The findings reveal that youth members apply circle and Y communication patterns, in line with Pace and Faules’ concept of downward, upward, horizontal, cross-channel, and informal communication. These patterns support an open communication system that fosters solidarity, consistent with Durkheim’s organic solidarity theory. The solidarity values identified include support, mutual help, respect, and a sense of belonging. Supporting factors consist of religious, social, cultural, and artistic activities, while inhibiting factors include differences of opinion and the emergence of group division.